Doing philosophy : from common curiosity to logical reasoning - Williamson, Timothy (Oxford, United Kingdom : Oxford University Press, 2018)
"In Doing Philosophy, Timothy Williamson tackles some of the key questions surrounding philosophy in new and provocative ways, showing how philosophy begins in common sense curiosity, and develops through our capacity to dispute rationally with each other. Discussing philosophy's ability to clarify our thoughts, he explains why such clarification depends on the development of philosophical theories, and how those theories can be tested by imaginative thought experiments, and compared against each other by standards similar to those used in the natural and social sciences. He also shows how logical rigor can be understood as a way of enhancing the explanatory power of philosophical theories."--
1. Introduction -- 2. Starting from Common Sense -- 3. Disputing -- 4. Clarifying Terms -- 5. Doing Thought Experiments -- 6. Comparing Theories -- 7. Deducing -- 8. Using the History of Philosophy -- 9. Using Other Fields -- 10. Model-Building -- 11. Conclusion: The Future of Philosophy.
Includes bibliographical references (pages 143-149) and index.
Keywords: Philosophy; Philosophy